The narcoleptic boy. - Stefani. (2010)
THE NARCOLEPTIC BOY is an animated short about a boy suffered from narcolepsy, in which making him fall asleep at inappropriate times and places, and his loyal dog who always takes care of him. In the first half of this heart-warming comedy, the boy always accidentally puts himself in danger and the dog is the one who has to save him. The tables are turned when his dog is put in danger and requires saving instead.